(untitled) (Revista Contexto & Educação, 2022)
The current study is a fragment of the final thesis for my Professional Master’s Degree in Professional and Technological Education (ProfEPT), entitled Educational Practices at the Escola Família Agrícola de Goiás: Pedagogy of Alternation and student training. The aim is to contextualize the educational practices of the Escola Família Agrícola de Goiás (Efago) through documents and literature review that support the Pedagogy of Alternation, contextualizing it with the school’s historical process of struggles and resistance. This study also aims to explain the didactic-pedagogical processes of the aforementioned school and how its work reflects on the integral formation of the students through the Pedagogy of Alternation proposal. Still in light of the theoretical background, the analysis of school documents and the reports obtained in the field research, they point out challenges that are obstacles for the Efago’s journey. The result evidenced that Efago, upon completing its 29 years of existence, has an essential role for the lives and future of rural students, as it links education with reality and seeks to promote the transformation of the subjects where they are inserted, through the integral and omnilateral training. Finally, this study raises other hypothesis for further researches, as the time frame, carried out during the Covid-19 pandemic, did not allow a more complete investigation in specific situations.